2013
DOI: 10.1128/mbio.00180-13
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Protein Motifs Direct Elongation Factor P-Mediated Translational Regulation in Salmonella enterica and Escherichia coli

Abstract: Elongation factor P (EF-P) is a universally conserved bacterial translation factor homologous to eukaryotic/archaeal initiation factor 5A. In Salmonella, deletion of the efp gene results in pleiotropic phenotypes, including increased susceptibility to numerous cellular stressors. Only a limited number of proteins are affected by the loss of EF-P, and it has recently been determined that EF-P plays a critical role in rescuing ribosomes stalled at PPP and PPG peptide sequences. Here we present an unbiased in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
159
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(180 citation statements)
references
References 47 publications
14
159
0
Order By: Relevance
“…In all cases, we were able to show that EF-P was able to efficiently relieve the translation stalling. Consistent with our findings was the identification of proteins containing PPP, PPG, or APP as being down-regulated when the genes encoding EF-P, YjeA, or YjeK were deleted in Salmonella (8,13). However, we did not observe any significant stalling in the absence of EF-P at non-diprolyl containing motifs, such as RME, YIR, PFF, YIRYIR, nor at the GSCGPG motif found in PoxB (Figs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In all cases, we were able to show that EF-P was able to efficiently relieve the translation stalling. Consistent with our findings was the identification of proteins containing PPP, PPG, or APP as being down-regulated when the genes encoding EF-P, YjeA, or YjeK were deleted in Salmonella (8,13). However, we did not observe any significant stalling in the absence of EF-P at non-diprolyl containing motifs, such as RME, YIR, PFF, YIRYIR, nor at the GSCGPG motif found in PoxB (Figs.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to PPP, PPG triplets also induce ribosome stalling in bacteria, which is rescued by EF-P (6). Moreover, a recent proteomics study identified APP, YIRYIR, and GSCGPG motifs as conferring EF-P dependent translation (13). Ribosome stalling has also been observed at PPA, PPD, PPE, PPN, PPW, APP, and WPP triplets during in vitro translation (7), however it was not shown whether EF-P can relieve the translational arrest at these triplets.…”
mentioning
confidence: 99%
“…The presence of polyproline motifs within proteins has been shown to be associated with a requirement for EF-P for their efficient translation. However, Hersch et al showed that not all proteins containing polyproline motifs depend on EF-P for their translation, while other, unknown peptide motifs may confer EF-P dependence, illustrating that our understanding of EF-P function is still limited (24). This study extends our knowledge of the roles that EF-P plays in bacterial physiology and virulence.…”
Section: Figsupporting
confidence: 66%
“…Although the full specificity of EF-P is unclear, runs of three or more prolines, as well as PPG and certain APP motifs, have been identified as sequences that are usually translated more efficiently in the presence of EF-P (22)(23)(24). Crystal structures show that EF-P displays a striking structural similarity to a tRNA (25).…”
mentioning
confidence: 99%
“…A prokaryotic ortholog of eIF5A termed EF-P was recently shown to stimulate translation of polyproline (Doerfel et al 2013;Hersch et al 2013;Ude et al 2013), and a similar function was identified for yeast eIF5A (Gutierrez et al 2013). Partial inactivation of a temperature-sensitive eIF5A variant confers reduced expression of reporter genes or authentic yeast ORFs containing homopolyproline stretches (Gutierrez et al 2013), leading to defects in fertility and polarized cell growth (Li et al 2014).…”
Section: Eif5a Promotion Of Peptide Bond Formationmentioning
confidence: 99%